2020
DOI: 10.1021/acsomega.0c01575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Model Construction of the Dense Medium Component Scaffold in Coal for Molecular Aggregate Simulation

Abstract: Coal as an important fossil energy has been comprehensively studied in terms of its structure, reactivity, and application. However, there are few publications reported about the formation mechanism of coal. In order to explore the molecular mechanism of the formation of the dense medium component (DMC) aggregate, which is extracted from coal, the molecular model of the DMC scaffold (DMC-S) was constructed based on a number of X-ray photoelectron spectroscopy, 13 C NMR, and ultimate analysis. Then, DMC-S was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The 13 C NMR peak positions and chemical shi assignments refer to the research results reported in the literature. [17][18][19] As can be seen from Fig. 1, the 13 C NMR peak tting curve of anthracite is divided into 11 peaks, corresponding to the type and content of carbon functional groups.…”
Section: Construction and Optimization Of Macromolecular Modelsmentioning
confidence: 99%
“…The 13 C NMR peak positions and chemical shi assignments refer to the research results reported in the literature. [17][18][19] As can be seen from Fig. 1, the 13 C NMR peak tting curve of anthracite is divided into 11 peaks, corresponding to the type and content of carbon functional groups.…”
Section: Construction and Optimization Of Macromolecular Modelsmentioning
confidence: 99%
“…In this instance, the original, regular, and round pores will become rough and irregular because the impact force will crack and destroy them, decreasing their roundness 21 . The coal skeleton supports the pores of the coal body, 25,26 and has a certain strength 27 , so the integrity of the coal skeleton will not be affected under the action of small loads. However, when excessive impact loads affect the coal body, a large amount of energy acts on the coal skeleton, resulting in the deformation or fracture of the coal skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In the directions of vertical and oblique bedding, the plane porosity and roundness become greater following the impact, while the roundness was reduced in the parallel bedding, indicating the strong impact anisotropy of the micro–nano‐pore structure of high‐rank coal. The impact load changes the pore morphology and size distribution of the coal body, improves the face ratio and roundness of the coal body, increases the pore diameter and depth, and stimulates the pore to become rounded and smooth. However, excessive impact load will cause small molecular compounds in the coal matrix to block the large pores, and also crack and destroy the original regular and smooth pores, thereby reducing the face rate and roundness value of the coal body 23–27 …”
Section: Discussionmentioning
confidence: 99%
“…Understanding the microstructure of coal is conducive to comprehending its reactivity and to exploring its diversity and discrepancy [ 9 , 10 ]. Famous coal models such as those by Wiser, Given, Shinn, and Wender have been used to exhibit the macromolecular structure of raw coal [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%